Comparison of Indigenous and Mechanical Conservation Technologies for Shifting Cultivation Agro-Ecology of North-eastern Himalaya - P. Chowdhury, Bidyut C. Deka, Priyanka Bihari; Saurav Saha, Sanjay Kumar Ray, Dibyendu Chatterjee* (Journal of the Indian Society of Soil Science, 2021)
Traditional shifting cultivation with reduced cycle aggravates soil erosion more rapidly in north-eastern India. To address this issue, an erosion plot experiment was conducted from January 2013 to December 2014 at Wokha district of Nagaland, India with five treatments viz., control (T1), bench terraces (T2), contour bunds (T3), bamboo fence (T4) and wooded log (T5). Soybean (cv. JS-335) was grown with the standard package and practices. The main objective was to find out the best suitable soil conservation measure to arrest the soil and nutrient loss. The annual soil erosion was measured the highest in treatment T1 (70.1 t ha-1) followed by T5 (25.2 t ha-1), T4 (13.5 t ha-1), T3 (6.20 t ha-1) and T2 (0.94 t ha-1) in the first year. In the second year, the extent of soil erosion was reduced, and it followed the order of T1 (50.7 t ha-1) < T5 (20.3 t ha-1) < T4 (8.92 t ha-1) < T3 (4.62 t ha-1) < T2 (0.54 t ha-1). Subsistent amount of clay, silt, sand, soil organic matter, major nutrients and micronutrients were lost in both the years. It was also found that the monetary loss in terms of only nitrogenous and potassium fertilizers was contributed 74.9 to 83.2% in the year 2013 and 50.7 to 70.8% in the year 2014, respectively. Considering all treatments across the years, bench terracing across the slope (T2) is found as the most suitable, but economic point of view, contour bund (T3) may be recommended for this region.